Acute health impact of wildfire-related and conventional PM2.5 in the United States: A narrative review - Yu Yu; William Zou; Michael Jerrett; Ying-Ying Meng (Environmental Advances, 2023)
The impacts of air pollution on public health have become great concerns worldwide. Particulate matter with an aerodynamic diameter small than 2.5μm (PM2.5), either from conventional sources such as traffic emissions or wildfire smoke, is among the most damaging air pollutants. Owing to increasing economic activities, consumption of natural gasses, and wildfires, the concentration of PM2.5 in the United States climbed back again. Compared with a large body of research summarizing PM2.5 chronic effects on health, fewer studies focused on its acute health impacts, especially from both wildfire-related and conventional sources. To fully capture the acute health impact of short-term PM2.5 exposure and estimate the associated economic cost in the United States, we conducted a narrative review of the available epidemiology studies on both sources and found a large body of evidence indicating the acute health impact of PM2.5 exposure, not only limited to cardio-respiratory diseases but also including depression, metabolic dysfunction, reproductive health effects such as placental abruption and gestational thyroid dysfunction. Although rare, some studies also indicated the acute impacts on work loss due to some symptom exacerbations that are not perceived as severe enough to search for medical assistance. More studies focusing on the acute impacts of PM2.5, especially from wildfire sources, on various outcomes such as neuropsychological, metabolic disorders, and sick leave and/or work productivity are needed to fully understand the extent of the acute health impact of PM2.5 exposure from both sources to inform the public health interventions.